Effects of 4 weeks of β-alanine supplementation on aerobic fitness in water polo players - Pinheiro Brisola, Gabriel Motta [UNESP]; Redkva, Paulo Eduardo [UNESP]; Pessoa Filho, Dalton Muller [UNESP]; Papoti, Marcelo; Zagatto, Alessandro Moura [UNESP] (Public Library of Science (PLoS), 2018)
The purpose of the present study was to investigate the ergogenic effects of 4 weeks of β- alanine supplementation on peak oxygen uptake (V. O 2peak ) and force associated with V. O 2peak (FV. O2peak) during a tethered swimming graded exercise test, and a three-minute all-out effort (3minALL-OUT) in water polo players. Twenty-two male national competitive level water polo players were randomly assigned to receive either 4 weeks of β-alanine (n = 11) or a placebo (n = 11) ((i.e., 4.8 g day -1 for 10 days, then6.4 g day -1 for 18 days, result, resulting in 163.2 g over 28 days). The participants performed the TSGET and 3minALL-OUT before and after the supplementation period. There were no significant interaction effects between-groups for any variable, however, the magnitude-based inferences analyses showed a possibly beneficial effect (74%) of β-alanine supplementation on FV. O2peak compared to placebo treatment (Δ% [post-pre] for Placebo group = -5.2%; Δ %[post-pre] for β-alanine group = +0.7%). Only the β-alanine group presented a significant reduction in V. O2peak expressed in absolute values (PRE = 3.3±0.6L min-1; POST = 3.0±0.4L min-1; p = .021). Similarly, only the β-alanine group presented a significant increase in critical force (PRE = 51.2±10.4N; POST = 56.5 ±13.1N; p = .044) and a reduction in the curvature constant parameter (W; PRE = 2998.0 ±1103.7N s; POST = 2224.6±1058.9N s; p = .049). Thus, we can conclude that 4 weeks of β-alanine supplementation presented mixed results in water polo players, indicating that this nutritional strategy may not be effective in improving parameters of the TS GET and 3min ALL-OUT . Copyright: 2018 Brisola et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.